Effect of ultrasound pre-treatment prior to enzymatic hydrolysis on physicochemical parameters of fish protein hydrolysates (FPH) extracted from side streams of Atlantic mackerel (Scomber scombrus) - Cropotova, Janna; Kvangarsnes, Kristine; Stangeland, Janne; Rustad, Turid (Frontiers in Sustainable Food Systems, 2024)
To produce fish protein hydrolysates (FPH) from fish raw material and side streams, enzymatic hydrolysis is commonly used. To optimize this traditional method of recovery and improve the physicochemical and functional parameters of recovered FPH, advanced non-thermal techniques like ultrasonication (US) can be applied as a pre-treatment step. The present study focused on evaluating the impact of US pre-treatment on the physicochemical parameters of FPH derived from mackerel side streams. Four experimental samples of FPH were produced: one control (without US pre-treatment) and three US pre-treated at power levels of 300 W, 450 W, and 600 W at 20 kHz before enzymatic hydrolysis. The findings revealed that FPHs from US-treated mackerel mince were lighter, less reddish, and contained a lower proportion of hydrophobic free amino acids ascribed to potentially lower bitterness. Moreover, FPH samples obtained from US-treated fish mince exhibited higher protein solubility and a greater degree of hydrolysis than the control (untreated). These functional improvements are attributed to the reduction in peptide particle size, leading to an increased presence of very small (<200 Da) and small peptides (500–2,000 Da) in FPH samples. Thus, it was shown that US pre-treatment of fish side streams before enzymatic hydrolysis can significantly improve protein solubility, degree of hydrolysis, and color parameters of FPH, while potentially affecting their bitterness through the reduction of hydrophobic free amino acids.